UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL DAUN SUJI (Dracaena angustifolia Roxb) TERHADAP EDEMA KAKI TIKUS PUTIH JANTAN GALUR WISTAR (PHARMACON, 2013)
ABSTRACTSuji (Dracaena angustifolia Roxb.) has been used empirically by the people of NorthSulawesi to cure the disease. Flavonoids and steroids in suji leaves suspected to haveantiinflammatroy effects. This study aims to examine the antiinflammatory effects of ethanolextract from suji leaves (Dracaena angustifolia Roxb.) on edema of white males wistar footinduced with 5% white egg solution, and to determine an effective dose of extract to decreasethe edema volume ofrat foot. The test was done using rat hind paw edema or esthablished anartificial inflammation in left foot of white male rats.The treatments were carried out on fivegroups, the positive control group was administered with diclofenac sodium, the negativecontrol group was administered with aquadest, and the extract groups were administered with100 mg/KgBB, 300 mg/KgBB and 1000 mg/KgBB of suji leaf extract. Edema volume weremeasured every hour for 7 hours using a glass tube. The average of edema volume (mL) andtime (hour) was plotted in a curve to form Area Under Curve (AUC). The AUC values wereused to calculate the percentage of antiinflammatory on each group compared to the negativecontrol group. Obtained data were analyzed by one-way ANOVA followed by LSD test withconfident level was 0,05. The result of this study indicate that suji leaf can reduce edemavolume of rat foot that induced with 5% white egg solution and antiinflamatory of ethanolextract from suji leaf 100 mg/KgBB by 33,19 %, 300 mg/KgBB by 14,04 % and 1000mg/KgBB by 5,80 %.Keywords: Suji(Dracaena angustifolia Roxb.), antiinflammatory, edema